USAGE OF RECLAIMED ASPHALT PAVEMENT AS A MIXTURE MATERIAL OF ASPHALT CONCRETE - WEARING COURCE (ACWC) - Ratna Handayani; Ahmad Faathir Wicaksono (Journal Innovation of Civil Engineering (JICE), 2020)
The objective of this research is to utilize Reclaimed Asphalt Pavement (RAP) as a mixture of hot asphalt AC-WC type. The new additional material is required such as an aggregate and asphalt to meet the technical performance which is based on Specification Bina Marga 2018 Revision 2. This research is started by analyzing the RAP. The result of RAP extraction process are aggregates and asphalt. Grading on aggregate were conducted for required grading envelope. If it failed to qualify for required grading envelope, new aggregate and new asphalt is needed. Therefore, the AC-WC mixture was composed by mixing with a variation of RAP which is 10%, 20% and 30%. From all of the mixing composition, only mixture with 30% of RAP and 70% of new materials is recommended for hot mixture which fulfilling the engineering criteria requirements.